PERANAN PEMBELAJARAN GEOGRAFI TERHADAP PEMAHAMAN PESERT DIDIK KELAS XI IPS DALAM MITIGASI BENCANA DI SEKOLAH SMA PEMBANGUNAN UNP PADANG - Syamsul Anwar; rery Novio (JURNAL BUANA, 2020)
This study aims to determine the ability of students to understand and apply the knowledge and skills of students in dealing with natural disasters through the role of geography learning in schools. This type of research is quantitative using a descriptive method approach. The sample and population in the study were all 118 students in class XI IPS at SMA Pembangunan Negeri Padang State University. The data collection methods were observation, questionnaire, interview and document study. The results of this study indicate that geography learning has a role in providing students' understanding of disaster mitigation. This can be seen the percentage shows 77%. In addition to geography learning, support from the school is very helpful in the form of supporting facilities for learning.